Pembelajaran Matematika dan Kemampuan Visual Imagery Peserta Didik dalam Materi SPLDV Di SMP - Hengky, Marianus; Jamiah, Yulis; T, Ahmad Yani; Fitriawan, Dona (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study was conducted to determine the ability of visual imagery in learning mathematics, especially the material of the system of linear equations of two variables in class VIII students of SMP Bruder Pontianak. The type of research used was descriptive qualitative. The subjects in this study were students of class VIII of Bruder Junior High School Pontianak who were selected by purposive sampling. Data collection through tests and interviews. The way to determine the ability of visual imagery is students by looking at indicators, namely receiving information, transforming and evaluating. The results of the research conducted show that the grouping of mathematical abilities is classified as high with a total of 2 students out of 30 by 6.67%, a group classified as medium with a total of 2 students out of 30 by 6.67% and a group that is in the low category as many as 26 students out of 30 by 86.66%. Thus, it can be concluded that students' visual imagery ability has not been said to be good or implemented when used in current mathematics learning in class VIII of Bruder Pontianak Junior High School.